2016
DOI: 10.1016/j.bjid.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

JC virus/human immunodeficiency virus 1 co-infection in the Brazilian Amazonian region

Abstract: JC virus (JCV) is a member of the Polyomaviridae family and is associated to a severe disease known as progressive multifocal leukoencephalopathy, PML, which is gradually increasing in incidence as an opportunistic infection among AIDS patients. The present study aimed to investigate the occurrence of JCV among HIV-1 carriers including their types and molecular subtypes and the possible association with disease. Urine samples from 66 HIV-1 infected subjects were investigated for the presence of the virus by am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Among HIV-1-infected patients, the excretion rate was 44.1% in Serbia, 32% in Brazil, and 47.6% in Italy. 16 , 19 , 28 , 32 The high frequency of polyomavirus excretion indicates that activation of viral reaction results from the interaction between polyomavirus and HIV. Differences in selection of primers and demographics of patients may account for the divergent results on the prevalence of JCPyV.…”
Section: Discussionmentioning
confidence: 99%
“…Among HIV-1-infected patients, the excretion rate was 44.1% in Serbia, 32% in Brazil, and 47.6% in Italy. 16 , 19 , 28 , 32 The high frequency of polyomavirus excretion indicates that activation of viral reaction results from the interaction between polyomavirus and HIV. Differences in selection of primers and demographics of patients may account for the divergent results on the prevalence of JCPyV.…”
Section: Discussionmentioning
confidence: 99%
“…Among other groups of co-infections with HIV-1, it was shown that JC virus apparently has no impact on the number of CD4 + T lymphocytes and HIV-1 plasma viral load [ 56 ], while GB virus C (GBV-C, currently classified as pegivirus, HPgV1) was associated with a decrease in HIV-1 viral load, an increase in CD4 + T lymphocytes and a possible protective effect in the progression of infection to AIDS [ 57 ].…”
Section: The Impact Of Hiv-1 In the Brazilian Amazon: From Description To Current Timesmentioning
confidence: 99%
“…Usually, a higher prevalence of JCV is observed in the Americas than on the African continent ( Chima et al, 1998 ; Stoner et al, 2000 ), a possible consequence of the intense miscegenation of Afro-descendants in Brazil and in the United States. The HIV-1 epidemic was also followed by a marked spreading of JCV among urban communities ( Nali et al, 2012 ; Cayres-Vallinoto et al, 2016 ).…”
Section: The Evidences Of Human Migration Accompanied By Infectious Amentioning
confidence: 99%